Profile of Antiemetic Activity of Netupitant Alone or in Combination with Palonosetron and Dexamethasone in Ferrets and Suncus murinus (House Musk Shrew) - Rudd, John A.; Ngan, Man P.; Lu, Zengbing; Higgins, Guy A.; Giuliano, Claudio; Lovati, Emanuela; Pietra, Claudio (Frontiers in Pharmacology, 2016)
Background and Aims: Chemotherapy-induced acute and delayed emesis involves the activation of multiple pathways, with 5-hydroxytryptamine (5-HT; serotonin) playing a major role in the initial response. Substance P tachykinin NK1 receptor antagonists can reduce emesis induced by disparate emetic challenges and therefore have a clinical utility as broad inhibitory anti-emetic drugs. In the present studies, we investigate the broad inhibitory anti-emetic profile of a relatively new NK1 receptor antagonist, netupitant, alone or in combination with the long acting 5-HT3 receptor antagonist, palonosetron, for a potential to reduce emesis in ferrets and shrews. Materials and Methods: Ferrets were pretreated with netupitant and/or palonosetron, or their combination, and then administered apomorphine (0.125 mg/kg, s.c.), morphine (0.5 mg/kg, s.c.), ipecacuanha (1.2 mg/kg, p.o.), copper sulphate (100 mg/kg, intragastric), or cisplatin (5-10 mg/kg, i.p.); in other studies netupitant was administered to Suncus murinus before motion (4 cm horizontal displacement, 2 Hz for 10 min). Results: Netupitant (3 mg/kg, p.o.) abolished apomorphine-, morphine-, ipecacuanha- and copper sulphate-induced emesis. Lower doses of netupitant (0.03-0.3 mg/kg, p.o.) dose-dependently reduced cisplatin (10 mg/kg, i.p.)-induced emesis in an acute (8 h) model, and motion-induced emesis in Suncus murinus. In a ferret cisplatin (5 mg/kg, i.p.)-induced acute and delayed emesis model, netupitant administered once at 3 mg/kg, p.o., abolished the first 24 h response and reduced the 24-72 h response by 94.6 %; the reduction was markedly superior to the effect of a three times per day administration of ondansetron (1 mg/kg, i.p.). A single administration of netupitant (1 mg/kg, p.o.) plus palonosetron (0.1 mg/kg, p.o.) combined with dexamethasone (1 mg/kg, i.p., once per day), also significantly antagonized cisplatin-induced acute and delayed emesis and was comparable with a once-daily regimen of ondansetron (1 mg/kg, p.o.) plus aprepitant (1 mg/kg, p.o.) in combination with dexamethasone (1 mg/kg, i.p.). Conclusion: Netupitant has potent and long lasting anti-emetic activity against a number of emetic challenges indicating broad inhibitory properties. The convenience of protection afforded by the single dosing of netupitant together with palonosetron was demonstrated and also is known to provide an advantage over other therapeutic strategies to control emesis in man.